Key paediatric messages from the 2017 European Respiratory Society International Congress. Issue 2 (25th May 2018) - Grigg, Jonathan; Barben, Jürg; Everard, Mark L.; Hall, Graham; Karadag, Bülent; Moeller, Alexander; Nenna, Raffaella; Priftis, Kostas N.; Rottier, Robbert J.; Terheggen-Lagro, Suzanne W.J.; Midulla, Fabio
In this article, the group chairs of the Paediatric Assembly of the European Respiratory Society (ERS) highlight some of the most interesting findings presented at the 2017 ERS International Congress, which was held in Milan, Italy. A review of highlights from selected presentations from #ERSCongress 2017 by the @ERStalk Paediatric Assembly http://ow.ly/ixZj30jzlVy